Expression Quantitative Trait Loci Analysis of Two Genes Encoding Rubisco Activase in Soybean(1)([W])([OA]) - Yin, Zhitong (American Society of Plant Biologists, 2010)
Rubisco activase (RCA) catalyzes the activation of Rubisco in vivo and plays a crucial role in photosynthesis. However, until now, little was known about the molecular genetics of RCA in soybean (Glycine max), one of the most important legume crops. Here, we cloned and characterized two genes encoding the longer α -isoform and the shorter β -isoform of soybean RCA (GmRCA α and GmRCA β, respectively). The two corresponding cDNAs are divergent in both the translated and 3 ′ untranslated regions. Analysis of genomic DNA sequences suggested that the corresponding mRNAs are transcripts of two different genes and not the products of a single alternatively splicing pre-mRNA. Two additional possible α -form RCA-encoding genes, GmRCA03 and GmRCA14, and one additional β -form RCA-encoding gene, GmRCA11, were also isolated. To examine the function and modulation of RCA genes in soybean, we determined the expression levels of GmRCA α and GmRCA β, Rubisco initial activity, photosynthetic rate, and seed yield in 184 soybean recombinant inbred lines. Correlation of gene expression levels with three other traits indicates that RCA genes could play an important role in regulating soybean photosynthetic capacity and seed yield. Expression quantitative trait loci mapping revealed four trans-expression quantitative trait loci for GmRCA α and GmRCA β. These results could provide a new approach for the modulation of RCA genes to improve photosynthetic rate and plant growth in soybean and other plants.